Novel supine isometric hamstring test: A reliability study - Gorman, B. T.; Kung, S.; Welch, N.; Squillante, A. (International Journal of Kinesiology & Sports Science, 2024)
Background: Hamstring strain injuries are highly prevalent, particularly when the hamstrings are in a lengthened position; however, monitoring strength deficits and fatigue throughout a season is currently difficult due to a lack of practical, reliable tests that do not cause undue fatigue.